Effects of Financial and Non-Financial Information Disclosure on Prices' Mechanisms for Emergent Markets: The Case of Bucharest Stock Exchange - Bogdan Dima; Ioan Cuzman; Ștefana Maria Dima (Cristea); Otilia Şărămăt (Journal of Accounting and Management Information Systems (JAMIS), 2013)
This paper investigates the impact of publicly disclosed information on market values for Romanian companies listed on Bucharest Stock Exchange, using as benchmark a more developed market, the Madrid Stock Exchange. The study is motivated by the European Union's decision to require the use of the International Financial Reporting Standards for the consolidated financial statements of all listed companies (Regulation EC 1606/2002) and by the 2007 Romanian adoption of the Markets and Financial Instruments Directive (MiFID) - which is the cornerstone of the European Commission's Financial Services Action Plan. Thus, we compare the value relevance of Internet disclosed information provided by annual and interim financial reports and other non-financial news in the decision making process of investors. In order to evaluate the overall impact of information disclosure, we built a global disclosure indicator according to the so-called Principal Components Analysis by including individual disclosure dummies. Empirical tests support our research hypothesis according to which there is a relative incremental value of a higher volume and a better quality of information, reflecting prices' overreactions even in the case of a market with imperfect trading mechanisms.
Keywords: M49; G10; 650; Disclosure; Valuation; Bucharest Stock Exchange; Madrid Stock Exchange